Designing The Concept of Innovation Profiling with Case Study - Indra Gamayanto; Sasono Wibowo; Florentina Esti Nilawati (IJISTECH (International Journal of Information System and Technology), 2022)
Innovation is very important in developing a smart city. Therefore, Innovation must be flexible to be applied when developing an area. We must not look only at one side in developing Innovation; Innovation must be broader than it should be and can provide significant changes in others' lives. This article is a long-term process, where this is gradual research, starting from a concept that will then be continued on a prototype and an application to measure a smart city's performance. The main problem is that there are still gaps and difficulties in understanding and implementing innovations. A definite basic concept is needed to execute Innovation right on target. In this article, the method used is from previous research, some formula from smart city 5.0. Moreover, this article's results are the basic concepts of Innovation, formulas, four basic types of Innovation, and seven types of innovation profiling: the innovation profiling framework. We have explained this research roadmap so that readers will know and understand the research process we are doing. It is very important because producing something must have a strong concept. What is produced can be more structured, systematic and on target in its application, especially smart city profiling.